Craniectomy and Cranioplasty Effects on Balance and Gait in Rehabilitation: A Retrospective Study - Leandra A. Stuckey, PT, DPT; Elizabeth E. Holland, PT, DPT; Miranda G. Gurra, MS; David Aaby, MS; Jennifer H. Kahn, PT, DPT (Archives of Rehabilitation Research and Clinical Translation)
Objective: To analyze changes in balance and gait in patients undergoing rehabilitation postcraniectomy and postcranioplasty, including comparison of outcomes across time periods, rate of change, and among diagnoses. Design: Retrospective cohort study. Setting: Inpatient rehabilitation. Participants: Fifty-three patients (mean age 52.3±16.9y; 62% male) with stroke, traumatic, or nontraumatic brain injury postcraniectomy or postcranioplasty. Interventions: Not applicable. Main Outcome Measures: Berg Balance Scale (BBS), Functional Gait Assessment (FGA), 6-minute walk test (6MWT), and 10-meter walk test (10MWT) were collected at baseline, first discharge, readmission, and final discharge. Results: Across the full rehabilitation course, all 4 outcomes improved: BBS, 17.9 points (95% confidence interval [CI], 12.7-23.2); FGA, 7.8 points (95% CI, 0.6-15.0); 6MWT, 141.0 m (95% CI, 89.0-192.0); and 10MWT, 0.381 m/s (95% CI, 0.188-0.575). All outcomes improved at postcraniectomy admission: BBS, 13.0 points (95% CI, 8.4-17.5); FGA, 4.0 points (95% CI. −1.65 to 9.65); 6MWT, 100.0 m (95% CI, 58.2-142.0); and 10MWT, 0.160 m/s (95% CI, 0.004-0.316). During leave of absence from rehabilitation, BBS decreased 6.3 points (95% CI, −11.8 to −0.8); FGA decreased 6.6 points (95% CI, −13.8 to 0.6); 6MWT decreased 19.2 m (95% CI, −73.5 to 35.2); and 10MWT increased 0.089 m/s (95% CI, −0.097 to 0.276). All outcomes improved at postcranioplasty admission: BBS, 11.3 points (95% CI, 6.6-16.0); FGA, 10.4 points (95% CI, 4.8-16.1); 6MWT, 59.4 m (95% CI, 14.1-105.0); and 10MWT, 0.132 m/s (95% CI, −0.039 to 0.303). Diagnosis was not associated with changes in outcomes. Conclusions: Gait and balance outcomes improved during postcraniectomy and postcranioplasty rehabilitation admissions but not immediately post cranioplasty.